2015
DOI: 10.1364/oe.23.033529
|View full text |Cite
|
Sign up to set email alerts
|

Automatic measurement of wood fiber orientation and knot detection using an optical system based on heating conduction

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. Abstract:In this paper, a new approach to computing the deviation of wood grain is proposed. To do this, the thermal conduction properties of timber are used (higher conduction in the fiber direction). Exciting the surface of the wood with a laser and capturing the thermal conduction using a thermal camera, an ellipse can be observed. Using a method similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…[5] Measured the length of ellipse minor and major axes on Japanese beech (Fagus crenata Blume) and sugi (Cryptomeria japonica D.Don) on sawn and planed wood surfaces, while rotating samples. They showed that, for both species, the grain angle measurement error on the planed samples was lower than on rough-sawn samples (maximum error of 4.6° for rough-sawn sugi), which is in accordance with [9] on Douglas fir. In [5], no analysis was provided regarding the major and minor axis length for the two species and two surface machining, and only one laser dot was used [10].…”
Section: Introductionsupporting
confidence: 64%
“…[5] Measured the length of ellipse minor and major axes on Japanese beech (Fagus crenata Blume) and sugi (Cryptomeria japonica D.Don) on sawn and planed wood surfaces, while rotating samples. They showed that, for both species, the grain angle measurement error on the planed samples was lower than on rough-sawn samples (maximum error of 4.6° for rough-sawn sugi), which is in accordance with [9] on Douglas fir. In [5], no analysis was provided regarding the major and minor axis length for the two species and two surface machining, and only one laser dot was used [10].…”
Section: Introductionsupporting
confidence: 64%
“…The resolution of the fibre orientation data obtained was 1 mm in the direction along the board and 4 mm in the transversal direction of the board. It is worth noting that because of the rough sawn surface of the Norway spruce and Douglas fir boards, the fibre orientation data was somewhat noisy, as described by Daval et al (2015). Figure 1 shows four wood surfaces (a-d) of a 150-mmlong part of one of the Norway spruce boards (the appearance would be similar for a board of Douglas fir) 50 × 100 mm in size, scanned by the industrial scanner.…”
Section: Determination Of Local Fibre Orientationmentioning
confidence: 99%
“…According to the research referred to above, the possibility of determining fibre orientation on board surfaces of softwood species using the tracheid effect is well documented. However, both Zhou and Shen (2003) and Daval et al (2015) found that this effect is more difficult to discern on hardwoods. As for oak, this was explained by the high density and short length of oak fibres, resulting in an insufficient diffusion of laser light and small size of the laser dot emerging on the board surface.…”
Section: Introductionmentioning
confidence: 98%
“…More recent results show the potential of such measurements for hardwoods, particularly for oak (Olsson et al 2018). Application of other NDT techniques to hardwoods, such as thermal conductivity measurement (Daval et al 2015) and automated visual analysis of the spindle patterns (Ehrhart et al 2018) has been on the research agenda.…”
Section: Introductionmentioning
confidence: 99%